Microeconomic Interventions after the Washington Consensus - Andrés Rodríguez-Clare (Inter-American Development Bank, Research Department, 2005)
This paper examines the microeconomic interventions used to complement Washington Consensus reforms in Latin America. It maintains that the kind of interventions currently in vogue in most countries lack a sound theoretical and empirical foundation or are applied in a manner likely to prove ineffective. Arguing that the countries of the region should engage in selective interventions aimed at discovering new profitable activities (horizontal policies) and at creating innovation clusters (vertical policies), the paper discusses how such a strategy could be implemented. Both horizontal and vertical policies are important, although the appropriate mix depends on a countrys stage of development. Pessimism about Latin American economies ability to undertake this more sophisticated set of microeconomic interventions is an exaggerated reaction to the problems of corruption and capture encountered by import-substitution policies. At least in some countries, there is scope for a carefully executed strategy of the type discussed here.
Keywords: 330; Wirtschaftsreform; Innovationspolitik; Industriepolitik; Internationaler Wettbewerb; Lateinamerika; Costa Rica